2018
DOI: 10.1177/1474704917749172
|View full text |Cite
|
Sign up to set email alerts
|

Intrasexual Competition and Height in Adolescents and Adults

Abstract: Intrasexual competition can be defined as the struggle between members of one sex to increase their access to members of the other sex as sexual partners. In our species, height is a sexually dimorphic trait probably involved in both intrasexual and intersexual selective processes. In the present research, we examined the relationship between height and individual differences in intrasexual competitiveness (i.e., the tendency to view same-sex interactions in general in competitive terms) in two populations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Notably, the results contrast with research showing that cyberbullying predicts perceived popularity, a reproductively relevant outcome (Wegge et al, ), and that dating is linked more strongly with physical bullying than with nonbullying overt aggression (Arnocky & Vaillancourt, ; Connolly et al, ; Dane et al, ; Houser et al, ). However, the associations between nonbullying cyber aggression and dating or sexual behavior are consistent with previous research suggesting that aggression tends to be directed toward equal or more powerful peers in intrasexual competition (Pellegrini, ; Polo et al, ). Moreover, the cyber context may be advantageous for aggression against dominant peers because it is indirect, nonphysical, and potentially anonymous (Kowalski et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Notably, the results contrast with research showing that cyberbullying predicts perceived popularity, a reproductively relevant outcome (Wegge et al, ), and that dating is linked more strongly with physical bullying than with nonbullying overt aggression (Arnocky & Vaillancourt, ; Connolly et al, ; Dane et al, ; Houser et al, ). However, the associations between nonbullying cyber aggression and dating or sexual behavior are consistent with previous research suggesting that aggression tends to be directed toward equal or more powerful peers in intrasexual competition (Pellegrini, ; Polo et al, ). Moreover, the cyber context may be advantageous for aggression against dominant peers because it is indirect, nonphysical, and potentially anonymous (Kowalski et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Power balances between perpetrators and victims may function differently in intrasexual competition than in bullying used for other purposes. For example, tall males are less likely than shorter males to compete against low‐power individuals for mates because they already possess traits preferred by females, such as physical strength and attractiveness (Polo, Fernandez, Muñoz‐Reyes, Dufey, & Buunk, ). Thus, dominant individuals may only engage in bullying to ensure that their dominance is not undermined when threatened, as seen in the nonhuman animal literature (see Weisfeld & Dillon, ).…”
Section: Introductionmentioning
confidence: 99%
“…This creates a natural constraint on the organism's adaptations and limits its fitness potential (Stearns, ). Although secondary sexual characters are not directly a part of the reproductive system of an organism, they are the product of sexual selection, giving fitness‐related advantages over the organism's rivals (Cornwallis & Uller, ; Polo, Fernandez, Munoz‐Reyes, Dufey, & Buunk, ). It has been suggested that secondary sexual traits such as large body size reliably signal the condition of a male by acting as a bioenergetic handicap (Folstad & Karter, ; Zahavi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Body size in human males is an important biological trait which affects a diverse range of outcomes such as attractiveness to potential mates and competition for resources (Patel & Devaraj, ; Pawłowski, Dunbar, & Lipowicz, ; Polo et al, ; Sell, Lukazsweski, & Townsley, ; Stulp & Barrett, ). In ontogeny, somatic growth and development of the immune system are thought to compete for the same resources, potentially impairing growth (Pawłowski, Nowak, Borkowska, Augustyniak, & Drulis‐Kawa, ; Stearns, ).…”
Section: Introductionmentioning
confidence: 99%
“…Height, as we know, is related to dominance 34 , and also to the likelihood of refereeing in more prestigious games 28 . Although taller men may be overall less competitive with the members of their own sex 35 , they may be more likely use sanctions as a form of competition in a high-stakes context. The Premier League and…”
Section: Does Referee Stature Relate To the Number Of Red Cards Per Gmentioning
confidence: 99%